Alternate fruit crops for sustainable food system - Singh, A K; Mishra, D S; Yadav, L P; Rane, Jagdish (Indian Farming, 2023)
India is origin of many fruit crops and the most of crops are limited to their growing region only. In spite of their high nutritional and medicinal properties their commercial cultivation is lacking. The tribal areas are full of biodiversity having natural vegetation which is not yet harnessed fully. Owing to which, a wide gap is existing between health and optimal use of natural sources of nutrients, i.e. alternate fruit crops (underutilized fruit crops). These fruits have many advantages like easier to grow and hardy in nature, producing a crop even under adverse soil and climatic conditions. So, exploitation of these fruit crops can be a solution of health and nutrition insecurity, poverty and unemployment. The underutilized crops have the potential to give health and economic security to the people by giving employment and by fetching good returns from their sale in raw form as well as value-added products. There are many temperate fruits hold considerable value and the potential of a veritable treasure of a large number of world’s fruits still remains to be explored and their potential is still not utilized which can play major role as alternate crops, ideally suitable for crop diversification, livelihood security to the poor masses dwelling in fragile ecosystem of the world.